Possibilidades e desafios do ensino de ciências por investigação no modelo remoto - Kanada, Laís Fernanda (Universidade Federal de São Carlos, 2022)
Science teaching in Brazil is in an unfavorable situation in relation to what would be ideal, mainly in the remote format that the pandemic has subjected all those involved in the educational process in the years 2020 and 2021. It is understood that this lag emphasized in remote teaching is a baggage of the lack of investment in education by the government, due to the low assimilation between the scientific content and the student, and by the absence of teaching methodologies that propitiate the insertion of young people in the scientific environment. For this reason, a teaching by investigation format, as the one proposed in this work, brings a possibility that reduces this problem by obtaining scientific knowledge through intellectual freedom of young people and for the investigations that they themselves raise based on a problem situation presented by the teacher. The present work sought to observe the possibilities and challenges of the application of teaching by investigation in the remote modality through the comparison of the parallel development of the activity in the face-to-face mode with students from the same classes of a public school in the city of Limeira/SP, where the author worked as a science teacher. As a result of this experience, two relevant points were raised. The first was that, regardless of whether applied in the remote or face-to-face model, teaching by investigation entourages more student participation and allows for more effective learning. And the second observation is that the remote model significantly reduces, almost eliminating, the student-teacher and student-student interaction, failing in the debates and joint construction of knowledge that the face-to-face model propitiates. This way, some adjustments can be made in order to allow a more expansive interaction, consequently increasing the quality of the methodology for the remote model of teaching, either soon with the technological evolution or, even, another chaos that requires this school isolation.
Possibilities and challenges of investigative science teaching in the remote model
Keywords: Metodologia pedagógica; Grau de liberdade intelectual; Pandemia; Aulas remotas; Recursos tecnológicos; Pedagogical methodology; Degree of intellectual freedom; Pandemic; Remote classes; Technological resources; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM